Death in early America - Seeman, Erik R. (History compass, 2019)
Interdisciplinary death studies was born in the 1970s amid critiques of the "high cost of dying" in the United States. In the field of history, this led to pioneering works that contrasted earlier, allegedly simple deathways with elaborate and expensive 20th-century practices. But because the broader societal critiques were imagined to apply principally to the White middle class, this narrowed the scope of historical inquiry to Euro-Americans. With the rise of Atlantic and Continental approaches to early American history in the 1990s, the history of death broadened to include American Indians and African Americans. Still, work remains to be done to bring those groups into the history of death in the 19th-century United States.